Case Report: Early experience with hypoxia-targeted SBRT-based partial tumor irradiation in large and bulky tumors - Penagaricano, Jose; Nakashima, Justyn Y. (Frontiers in Oncology, 2025)
Large and bulky tumors possess poor prognostic characteristics that make tumor control difficult. Stereotactic body radiotherapy (SBRT)-based partial tumor irradiation targeting the hypoxic segment (SBRT-PATHY) has been described as a spatially fractionated radiotherapy technique that induces both bystander and abscopal effects by sparing the peritumoral immune microenvironment, thus minimizing the negative effects of radiation-induced lymphopenia. These case reports aim to present our early experience with four cases utilizing SBRT-PATHY at our institution.